5G Mobile Communications - Xiang, Wei.; Zheng, Kan.; Shen, Xuemin (Sherman).; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
.
An Overview of 5G Requirements -- Spectrum Analysis and Regulations for 5G -- Spectrum Sharing for 5G -- Massive MIMO Communications -- Millimeter-Wave Communications for 5G Mobile Systems -- Non-orthogonal Multiple Access (NOMA) for 5G -- New Multi-carrier Modulation for 5G -- Fundamentals of Faster-than-Nyquist Signaling -- Generalized Frequency Division Multiplexing: A Flexible Multi-carrier Waveform for 5G -- Spectrally Efficient Frequency Division Multiplexing for 5G -- Full-duplex Wireless Communications for 5G -- Device-to-Device Communications over 5G Systems -- M2M Communications for 5G -- Design Techniques of 5G Mobile Devices in the Dark Silicon Era -- Ultra-Dense Network Architecture and Technologies for 5G -- 5G RAN Architecture - C-RAN with NGFI -- User-centered wireless network for 5G -- Energy Harvesting based Green HetNets for 5G -- Resource Management in Sustainable Green HetNets with Renewable Energy Sources -- Resource Allocation for Cooperative D2D Communication Networks -- Fog Computing and its Applications in 5G -- A Conceptual 5G Vehicular Networking Architecture -- Communications Protocol Design for 5G Vehicular Networks -- Next-Generation High-Efficiency WLAN -- Shaping 5G for the Tactile Internet.
Keywords: Telecommunication; Computer networks .; Communications Engineering, Networks; Computer Communication Networks